1983
DOI: 10.1002/1097-4679(198301)39:1<90::aid-jclp2270390117>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

A factor analysis of the social interest index-revised

Abstract: Factor analyzed the Social Interest Index–Revised (SII‐R), an instrument developed to measure the level of social interest that an individual has attained in each of four life task areas. Four factors (N = 308) were defined: A self‐significance factor, a love factor, a freindship factor. The four factors combined accounted for 38.8% of the total variance. The results supported the empirical validity of the scale and provided further evidence for researchers who are seeking to define social interest in measurab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The areas of greatest weakness seem to be its muddled factor structure (e.g., inappropriate factor loadings; Leak, 1982), and the factor structures found across studies have proven difficult to replicate (Leak, 1982; Watkins, 1994). Some studies have found a four-factor solution (Zarski, Bubenzer, & West, 1983) whereas others have found a five-factor solution (Zarski, West, & Bubenzer, 1981). Furthermore, some studies have found the existence of a general social interest factor (Greever et al, 1973), whereas others have not (Leak, 1982).…”
Section: Measurement Of Social Interest With the Social Interest Inde...mentioning
confidence: 99%
“…The areas of greatest weakness seem to be its muddled factor structure (e.g., inappropriate factor loadings; Leak, 1982), and the factor structures found across studies have proven difficult to replicate (Leak, 1982; Watkins, 1994). Some studies have found a four-factor solution (Zarski, Bubenzer, & West, 1983) whereas others have found a five-factor solution (Zarski, West, & Bubenzer, 1981). Furthermore, some studies have found the existence of a general social interest factor (Greever et al, 1973), whereas others have not (Leak, 1982).…”
Section: Measurement Of Social Interest With the Social Interest Inde...mentioning
confidence: 99%
“…Leak concluded that there existed no evidence for a global social interest factor as had been reported by Greever, Tseng, and Friedland (1973), and Zarski, West, and Bubenzer (1981). Furthermore, the factor analysis did not reveal any factor corresponding to the work task and The object dimension refers to the object of the social interest.…”
Section: A Review Of the Social Interest Index Researchmentioning
confidence: 82%
“…Because of the small sample size (N = 83) used in the factor analysis the validity of their results is questionable. In the first subsequent study, Zarski, West, and Bubenzer (1981) obtained a sample of 318 Masters' level students (152 male and 166 female) with a mean age of 32 years. A factor analysis with principal axis solution and varimax rotation was performed.…”
Section: A Review Of the Social Interest Index Researchmentioning
confidence: 99%